KERIS : Struktur-Fungsi-Aktivitas (Kajian dengan Pendekatan Etnoarkrologi) - Agus Irawan; Soedjijono; Ninik Indawati (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2021)
This study aims to understand the Keris as a historical and cultural artifact of the Indonesian nation from the perspective of Structure-Function-Activities from the past as well as the contemporary era. This research is a qualitative study, with the Ethnoarchaeological Approach to study the Keris, with the object of the Keris Artifact research collection of the Association of Society